2021
DOI: 10.1155/2021/9994872
|View full text |Cite
|
Sign up to set email alerts
|

Breaching the Bridge: An Investigation into Doctor‐Patient Miscommunication as a Significant Factor in the Violence against Healthcare Workers in Palestine

Abstract: Background. Workplace violence is a common issue worldwide that strikes all professions, and healthcare is one of the most susceptible ones. Verbal and nonverbal miscommunications between healthcare workers and patients are major inducers for violent attacks. Aim. To study the potential impact of verbal and nonverbal miscommunications between the patients and healthcare workers upon workplace violence from the patients’ perspectives. Methods. A descriptive cross-sectional study was performed from November to D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In another study conducted in 2021, 7.2% of the study population reported participating in nonverbal violence and 19.6% participating in verbal violence against the healthcare workers 27 . Such events are thought to be under‐reported and are majorly attributed to the absence of appropriate consequences against them 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study conducted in 2021, 7.2% of the study population reported participating in nonverbal violence and 19.6% participating in verbal violence against the healthcare workers 27 . Such events are thought to be under‐reported and are majorly attributed to the absence of appropriate consequences against them 15 .…”
Section: Discussionmentioning
confidence: 99%
“…15 In another study conducted in 2021, 7.2% of the study population reported participating in nonverbal violence and 19.6% participating in verbal violence against the healthcare workers. 27 Such events are thought to be under-reported and are majorly attributed to the absence of appropriate consequences against them. 15 This lack of a healthy and safe working environment negatively affects the mental health of HCWs, their patient care and willingness to continue their job.…”
Section: Palestinementioning
confidence: 99%
“…This was referred to as the political and economic situation [ 14 ]. Furthermore, the doctor–patient miscommunication in Palestine [ 15 , 16 ], as well as the coronavirus-19 (COVID-19) pandemic, added an extra layer of challenge to the Palestinian health care sector [ 17 , 18 , 19 ]. These challenges exploited obstacles to improving the performance of HCOs in Palestine and highlighted the importance of involving HCWs in the process of improving the performance of HCOs through a better understanding of Palestinian HCW perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…Visitors, as well as patients themselves were the most common perpetrators of on job violence against HCPs [ 4 , 9 , 12 , 15 – 17 ]. Miscommunication between patient and doctor are commonly the cause of escalating into violent incidents [ 19 ]. Moreover, only half of on job violence victims reported the incident.…”
Section: Introductionmentioning
confidence: 99%